Transformation of SCLC into NSCLC-squamous type with invasive fungal co-infection - Anggraeni, Rizki Diah; Setyawan, Ungky Agus; ugiri, Yani Jane R. S; Erawati, Dini Rachma; Yudhanto, Hendy Setyo (Edelweiss Applied Science and Technology, 2025)
Small Cell Lung Cancer (SCLC) is a neuroendocrine tumor with and poor prognosis. Transformation commonly occurs from NSCLC to SCLC, that caused by chemotherapy, immunotherapy, and targeted therapy resistance. This case shows a 5% rare case transformation from SCLC to NSCLC. A 69-year-old man had hemoptysis, dyspnea, and chest pain for a month. In 2017, the history of SCLC received 6 series of cisplatin-etoposide chemotherapy. CT-Scan Thorax RECIST was stable disease, and the rest of the treatment was. In April 2022, RECIST showed that the mass increased. KOH sputum obtained hyphae and conidia. Forceps biopsy found Aspergillus. Re-biopsy was squamous cell carcinoma. SCLC transformation is characterized by TP53 and RB1 gene mutations. Interferon-ỿ (INFỿ) production impairment due to IL12RB1 mutation caused macrophages to eliminate intracellular fungi. Fungal interaction (integrin-β1) on alveolar epithelial cells increases EGFR activation, cell damage, and the development of fungal invasion. Patient was given fluconazole and carboplatin-paclitaxel chemotherapy 6 series, then maintenance paclitaxel, currently stable.